Truth As a Concept of Islamic Education: A Study on the Thoughts of Syed Muhammad Naquib Al-Attas - Enayatullah Dadman; Wafiullah Aminzai; Azizullah Amin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the concept of truth within Islamic education through the intellectual framework of Syed Muhammad Naquib Al-Attas. The primary objective is to analyze how Al-Attas conceptualizes truth (ḥaqq) and its role in shaping the aims, content, and methodology of Islamic education. The research employs a qualitative, library-based methodology, drawing upon Al-Attas’s major works, including Islam and Secularism and The Concept of Education in Islam, alongside relevant secondary sources. A thematic analysis is used to identify key patterns and principles related to truth and knowledge. The findings reveal that Al-Attas views truth as a metaphysical and epistemological reality grounded in divine revelation, rather than merely empirical or relative constructs. He emphasizes that true education (ta’dīb) integrates knowledge, ethics, and spiritual development, aiming to produce a balanced individual who recognizes the proper place of things in the order of creation. The study further shows that the loss of adab leads to confusion and the distortion of truth in modern education systems. Therefore, re-centering truth based on the Islamic worldview is essential for reforming contemporary Muslim education. This research highlights the enduring relevance of Al-Attas’s thought in addressing current educational challenges.